Soldier-portable battery supply : foreign dependence and policy options - Silberglitt, Richard (RAND, 2014)
Batteries are a ubiquitous presence in equipment carried by soldiers and critical to the performance of electronic devices such as radios, computers, night-vision goggles, and laser range finders. These batteries are supplied by a variety of firms, and mostly assembled from cells that are acquired through a supply chain that is driven by commercial applications to mobile phones, laptop computers, tablets, and other electronic devices, and is predominately based in Asia. RAND found that government researchers and program managers and representatives of military battery suppliers have concerns associated with this foreign-dependent supply chain. The report discusses alternative policy options to address these concerns, without evaluating the benefits versus costs of these policy options.